Social Robotics Guidelines - Ramírez Benavides, Kryscia Daviana (2019)
Human interactions are affected by society's norms and cultural criteria. Individuals expect certain behaviors from other people, who have an obligation to act according to the expected behavior in the cultural and social context that surrounds them. Giving robots the ability to interact with humans, in human terms, is a great open challenge. People are willing to accept robotic systems in everyday life when robots engage in socially desirable (correct) behaviors with benevolent interaction styles (safe physical interaction). In addition, allowing robots to reason in social situations, involves a set of social norms that generate expectations, which can improve the dynamics of interactions between humans and robots, and the processes of selfassessment of robot behavior. In this article, we present a set of requirements for a more secure and socially correct physical interaction the robot with people, which is dependent on cultural criteria.